(untitled) (Bangladesh Journal of Urology, 2020)
Objectives: To determine the effectiveness of transurethral resection of bladder neck in the management of primary bladder neck obstruction (PBNO) in female Patients and Methods: This prospective study has been done with thirty female patients aged from 27 to 48 years who were presented with difficult micturition or urinary retention. These patients had unremarkable physical findings with normal perianal sensation, anal sphincter tone and lower extremity reflexes. Patients associated with cystocele, meatal stenosis, stricture urethra, urethral caruncle and urethral diverticula that may lead to mechanical bladder outflow obstruction were excluded from the study. Preoperative investigations include uroflowmetry, ultrasonography, serum creatinine, urethrocystoscopy with simultaneous “water flow test” was done. Seven patients presented with obstructed voiding symptom without renal impairment (serum creatinine, mean±SEM 1.24±0.04) and were initially treated with á-blocker (category A). Among the other 23 patients those had renal impairment 18 presented with near retention and these patients were on indwelling catheterization before operation (category B, serum creatinine, mean±SEM 2.72±0.13).Rest of the 5 patients presented with nausea, vomiting, and disorientation in addition to near retention and were put on haemodialysis along with indwelling catheterization to reach near normal creatinine level before operation(category C, serum creatinine, mean±SEM,9.34±0.96 ). PBNO causing voiding difficulty were diagnosed in all the cases and were undergone transurethral bladder neck resection (BNR). Three months after operations, their pre- and post-operative symptoms were analyzed, and serum creatinine levels, ultrasonographic findings (MCC, PVR), uroflowmetric study were compared. Results: Twenty-nine (96.33%) Patients become symptom free. Their average pre- and post-operative values of MCC (Maximum Cystometric Capacity), PVR (Post Voidal Residual urine), Qmax (Peak urinary flow during uroflowmetric study, Serum creatinine level were changed from 679.50 to 482.17ml, from 574.50 to 29.37ml, from 8.43 to 29.37ml/sec, from 3.48 to 1.13 mg/dl respectively. One patient (3.33%) did not continent ever postoperatively. One patient had become dry after using pad for stress incontinent for one month only. Serum creatinine level of category C patient did not reach to the normal level (post operative creatinine level Mean±SEM,2.8±0.15)within this three moths follow up period. Conclusions: Our short term follow-up suggests that judicious Transurethral BNR is effective in relieving voiding difficulty due to primary bladder neck obstruction in female. A thorough gynaecological, neurological and urological examination is essential along with uroflowmetric, ultrasonographic and cystoscopic study to reach a correct diagnosis and making a treatment plan. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.23-28